Análisis Jurídico de la Ordenanza Municipal que regula y controla la protección, tenencia, comercialización y cuidado responsable de canes y mascotas que garantice sus derechos en el área urbana y centros poblados del cantón Celica. - Quezada Montalván, María José (2024)
Given the challenges in Celica canton to ensure animal welfare, it was crucial to address the lack of resources and public awareness. This implied strengthening the allocation of resources, training the staff of the competent public entities on the subject, and raising community awareness about responsible animal care, with the aim to overcome the barriers that limited their welfare and guarantee their integral protection. To achieve the established objectives, a methodology was used which consisted of employing qualitative methods such as grounded theory, descriptive research, and bibliographic research. The instruments employed to collect data were surveys and interviews. The empirical and maieutic methods guided the research towards specific conclusions, allowing the collection of accurate information on compliance with the municipal ordinance and citizen awareness regarding animal welfare. This research methodology focused on a purposive sample of 30 citizens of the cantonal head of Celica. From the results, it was possible to obtain significant information on the research topic, revealing that 93% of respondents are aware of animal rights, although 27% are unaware of the existence of the regulations. The majority own pets, prefer dogs and support free sterilization. Despite the general perception of abandonment and the need for more resources from the Municipal GAD, initiatives such as the deworming campaign that highlight significant efforts in animal care and disease control. The results allow to conclude that there is a high awareness of animal rights and support for programs such as free sterilization; however, they also highlight deficiencies in the dissemination and application of the municipal ordinance. Therefore, it is necessary to improve communication and education about the regulations, as well as increase resources and support for their implementation. Although citizen initiatives are valuable, greater commitment and collaboration between the community and local authorities are crucial to ensure a safer and more responsible urban environment for animals and their owners.